2017
DOI: 10.18632/oncotarget.14424
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile colonization in preoperative colorectal cancer patients

Abstract: The entire process of Clostridium difficile colonization to infection develops in large intestine. However, the real colonization pattern of C. difficile in preoperative colorectal cancer patients has not been studied. In this study, 33 C. difficile strains (16.1%) were isolated from stool samples of 205 preoperative colorectal cancer patients. C. difficile colonization rates in lymph node metastasis patients (22.3%) were significantly higher than lymph node negative patients (10.8%) (OR=2.314, 95%CI=1.023-5.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
(38 reference statements)
3
36
0
Order By: Relevance
“…17,18 Large numbers of studies have shown that CRC patients have characteristic microbes, including Fusobacteria, Streptococcus, and Clostridium in their intestines. [19][20][21][22] Gut microorganisms are involved in the development and progression of CRCs through many pathways such as through the induction of inflammation and biosynthesis of genotoxins. 23,24 Recent studies have suggested that the occurrence of CRCs is not only the function of a single microorganism, but also the result of the disruption of dynamic equilibrium of the gut microecology.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Large numbers of studies have shown that CRC patients have characteristic microbes, including Fusobacteria, Streptococcus, and Clostridium in their intestines. [19][20][21][22] Gut microorganisms are involved in the development and progression of CRCs through many pathways such as through the induction of inflammation and biosynthesis of genotoxins. 23,24 Recent studies have suggested that the occurrence of CRCs is not only the function of a single microorganism, but also the result of the disruption of dynamic equilibrium of the gut microecology.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the incidence rate of CDI in CRC patients. In recently, a team of researchers from Memorial Sloan Kettering Cancer Center and China investigated the pattern of C. difficile colonization in preoperative CRC patients [4], and the changes in the gut microbiota composition from the CRC would be associated with increased risk for CDI. But there are no comparative studies for the incidence rate between RG and CG, at least in our review.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the prevalence of C. difficile colonization is high in preoperative colorectal cancer patients, and the colonization is not acquired in the hospital. Antibiotic susceptibility testing showed all isolates were susceptible to vancomycin and metronidazole [24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the prevalence of C. difficile colonization is high in preoperative colorectal cancer patients, and the colonization is not acquired in the hospital. Antibiotic susceptibility testing showed all isolates were susceptible to vancomycin and metronidazole [24].We must note that all interventions in our institution were performed in an elective manner, being a known fact that patients undergoing an emergency operation are at higher risk of developing CDI than those having operations performed electively [25]. These types of interventions are usually followed by a number of postoperative complications.…”
mentioning
confidence: 99%